An aptamer and Au/Si CCA based SERS sensor for ultra-sensitive detection of Vimentin during EMT in gastric cancer - Cheng, Lingling; Xu, Jianlin; Yuan, Hua; Zhao, Qihao; Yue, Wei; Ma, Shuang; Lu, Weimin (Frontiers in Bioengineering and Biotechnology, 2023)
In this study, a surface-enhanced Raman scattering (SERS) sensor based on a functionalized Au/Si cap-cone array (Au/Si CCA) was constructed using the identity-release strategy to detect Vimentin changes during epithelial-mesenchymal transition (EMT) in gastric cancer (GC). The periodic structure of Au/Si CCA, which can form "hot spots" with high density and regular arrangement, is a substrate with excellent performance. Au/Si CCA was functionalized with aptamers as the capture substrate, and Au nanocubes (AuNCs) were modified with 5-carboxyfluorescein (5-FAM) labelled complementary strand as SERS probe. The capture substrate and SERS probe were assembled by hybridization, and the SERS signal intensity of 5-FAM was greatly enhanced. The binding of Vimentin to the aptamer resulted in a broken connection between the SERS sensor Au/Si CCA array and AuNCs, which resulted in a decrease in the signal intensity of 5-FAM. The identity-release strategy requires only a simple step of reaction to achieve rapid detection of target proteins, which has clinical practicability. Using this protocol, the concentration of Vimentin in GES-1 cells could be successfully detected, and the detection limit was as low as 4.92 pg/mL. Biological experiments of Vincristine, Oncovin (VCR)treated GES-1 cells effectively mimicked the EMT process, and Vimentin changes during EMT could be accurately detected by this method. This study provides a selective, ultra-sensitive and accurate assay for Vimentin detection, which may provide a means for the future detection of EMT process in GC.